The Evaluation of Spray Drying Process Condition on the Characteristics of Xylitol Powder from Oil Palm Empty Fruit Bunches - Mardawati, Efri; Rialita, Tita; Suryadi, Edy; Rahmah, Devi Maulida; Anggraini, Sulistina; Bindar, Yazid (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2020)
AbstractXylitol is a low-calorie, natural sweetener which has similar sweetness properties to sucrose. Xylitol can be produced from the hemicellulose hydrolysate of Oil Palm Empty Fruit Bunches (OPEFB). Several steps required for this process, including pretreatment, the hydrolysis of xylan to xylose and the reduction of xylose to xylitol. In a commercial market, xylitol is commonly found in the form of powder in order to maintain its distribution stability and practicality. The spray drying method is a drying method that is mostly used in dry or powder products manufacturing industry. This research aims to investigate the effect of spray drying and to determine proper inlet temperature and maltodextrin concentration on xylitol powder characteristics that are similar to the quality of commercially produced xylitol. Randomized Group Design Method is a data processing method used in this research which consisted of two factors: inlet temperature (160 oC and 180 oC) and maltodextrin concentrations (20%, 25%, and 30%). Based on the result of the research, the inlet temperature significantly affected the water content, solubility, hygroscopic levels and calorie content. Results also showed that maltodextrin concentration had a significant effect on the hygroscopic levels, water content and calorie content. Xylitol powder similar to the commercially produced xylitol was obtained from the inlet temperature of 160 oC and 20% of maltodextrin, with the water content of 5.17%, hygroscopic levels of 8.55%, solubility of 99.346%, calorie content of 2.71 cal/g and xylitol content of 0.034 g/L.Keywords: inlet temperature, maltodextrin, oil palm empty fruit bunch, spray drying, xylitol